Internalization of Tasamuh (Tolerance) Values in Educational Interactions: A Thematic Study of Religious Freedom Verses - Bakhri, Alim; Musyarif, Musyarif (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to examine the internalization of the value of tasamuh (tolerance) in the educational interaction between teacher and student through a thematic interpretation approach to the verse لَا إِكْرَاهَ فِي الدِّينِ (QS. Al-Baqarah: 256). The background of this research is based on the importance of education as a means of forming tolerant character in a pluralistic society, and there are still challenges in the implementation of tolerance values in the school environment. The method used is a qualitative approach with the maudhuiy (thematic) tafsir method, through the analysis of relevant Qur'anic verses, classical and contemporary interpretations, and tolerance education literature. The results of the study show that the verse لَا إِكْرَاهَ فِي الدِّينِ contains the principle of religious freedom which is the theological foundation for the development of tolerance in education. The internalization of tasamuh values can be carried out through an approach that integrates cognitive, affective, and behavioral aspects, with teachers playing the role of facilitators and role models. Implementation strategies include interactive dialogue, experiential learning, positive reinforcement, and value reflection. The application of this pedagogical model has been proven to be able to create an inclusive, harmonious classroom environment, and support the moral and social development of students.